Determinants of engagement in muscle-strengthening activities among children and adolescents: insights from a large-scale school-based study - Sheng, Hongtao; Ge, Bin; Li, Yang; Xu, Zehan; Yang, Xingyi; Wang, Wenjun; Yan, Jin (Frontiers in Public Health, 2025)
ObjectivesThis study examined the sociodemographic factors associated with muscle-strengthening exercise (MSE) participation in a sample of Chinese school-aged children.MethodsA cross-sectional survey was conducted in March 2021, comprising 67,281 students from public schools in Shenzhen through a multistage sampling method. The survey collected data on MSE participation, sociodemographics, family and educational information, and other aspects. A three-level mixed multilevel effect model was performed to analyze the associations between the selected sociodemographic characteristics and MSE participation. Results were presented using odd ratios (OR) with 95% confidence intervals (CI).Results38.6% of participants met the MSE guidelines. In models of adherence to MSE guidelines and MSE days, boys were more likely to participate in MSE (OR = 1.31, 95%CI: 1.27–1.36, p < 0.001) than girls. Compared to primary school students, junior middle school students (OR = 1.60, 95%CI: 1.47–1.74, p < 0.001) were more likely to participate in MSE, whereas high school students (OR = 0.61, 95%CI: 0.51–0.73, p < 0.001) participated less frequently. Socioeconomic status (both OR = 1.07, 95%CI: 1.01–1.13, p < 0.001) was positively associated with MSE participation. Participants who perceived their weight as “about the right weight” or “slightly overweight” were most likely to participate in MSE. Weight satisfaction was negatively associated with guideline adherence, with those “very dissatisfied” with their weight being more likely to adhere. Positive associations between sports club participation and sports equipment satisfaction with MSE participation were also found. Other factors, such as ethnicity and parental education level, showed no significant association.ConclusionMSE participation is correlated by sociodemographic, behavioral, and self-perception factors, particularly sex, age, socioeconomic status, sports club involvement, and weight perception. Interventions to enhance MSE participation should target the important identified factors. Future studies should consider using longitudinal designs to strengthen understanding of MSE, further aiding in developing relevant and effective interventions.